A Frustrated Phosphane–Borane Lewis Pair and Hydrogen: A Kinetics Study. Issue 34 (19th July 2016) - Özgün, Thomas; Bergander, Klaus; Liu, Lei; Daniliuc, Constantin G.; Grimme, Stefan; Kehr, Gerald; Erker, Gerhard
Abstract: The energy profile of a frustrated Lewis pair (FLP) dihydrogen splitting system was determined by a combined experimental kinetic and DFT study. A trimethylene‐bridged phosphane–borane FLP was converted into its endothermic H2 ‐cleavage product by sequential H + /H − addition. The system could be handled at low temperature, and the kinetics of the H2 elimination were determined to give a rate constant of k HH, exp (299 K)=(2.87±0.1)×10 −4 s −1 in solution. The primary kinetic isotope effects were determined; for example, ( k HH / k DD )exp =3.19. The system was accurately analyzed by DFT calculations. Abstract : Retro‐kinetics : An evaluation of a dihydrogen splitting reaction utilizing a phosphane–borane frustrated Lewis pair was carried out by theory and experiment. The evaluation used the reverse reaction, namely, H2 elimination from a PH + /BH − zwitterion. H2 elimination kinetics gave a rate constant k HH, exp (299 K)=(2.87±0.1)×10 −4 s −1, and kinetic isotope effects were determined; for example, ( k HH / k DD )exp =3.19.